Fungal burden in waste industry: an occupational risk to be solved - Viegas, Carla (2015)
High loads of fungi have been reported in different types of waste management plants. This study intends to assess fungal contamination in one waste-sorting plant before and after cleaning procedures in order to analyze their effectiveness. Air samples of 50 L were collected through an impaction method, while surface samples, taken at the same time, were collected by the swabbing method and subject to further macro- and microscopic observations. In addition, we collected air samples of 250 L using the impinger Coriolis μ air sampler (Bertin Technologies) at 300 L/min airflow rate in order to perform real-time quantitative PCR (qPCR) amplification of genes from specific fungal species, namely Aspergillus fumigatus and Aspergillus flavus complexes, as well as Stachybotrys chartarum species. Fungal quantification in the air ranged from 180 to 5,280 CFU m−3 before cleaning and from 220 to 2,460 CFU m−3 after cleaning procedures. Surfaces presented results that ranged from 29 × 104 to 109 × 104 CFU m−2 before cleaning and from 11 × 104 to 89 × 104 CFU m−2 after cleaning. Statistically significant differences regarding fungal load were not detected between before and after cleaning procedures. Toxigenic strains from A. flavus complex and S. chartarum were not detected by qPCR. Conversely, the A. fumigatus species was successfully detected by qPCR and interestingly it was amplified in two samples where no detection by conventional methods was observed. Overall, these results reveal the inefficacy of the cleaning procedures and that it is important to determine fungal burden in order to carry out risk assessment.